PRINCIPLES OF BALANC E IN THE FRANCHISE A GREEMENT VIEWED FROM ARTICLE 1338 OF THE CIVIL CO DE - Gilalo, J Jopie (DE'RECHTSSTAAT, 2015)
ABSTRACT Business franchise is already a business activity to invest quickly in a way the distribution system and marketing of a product of goods and or services. Shape franchise made with a covenant between franchisor and franchisee. Problems in the agreement, if the position between the rights and obligations of both parties had been balanced in the implementation of the bonds they created. Franchise agreement is a contract specially (not named). Based on the Law of Treaties in Indonesia Franchise agreements as was as contract law, which refers to Article 1338 of the Civil Code with the fulfillment of the terms of contract law. In addition, the legal umbrella which provides franchise business, namely in the form of regulations issued by the government for guarantees in this business, even though the principle of balance in terms of an agreement, the franchise agreement has not been providing some balance to the franchise yet.